Filsafat Ketuhanan Dalam Purana - I Putu Agus Aryatnaya Giri; I Ketut Wiratmaja (Genta Hredaya: Media Informasi Ilmiah Jurusan Brahma Widya STAHN Mpu Kuturan Singaraja, 2020)
The concept of divine philosophy (theology) of Hinduism in literacy is actually very much found in the Vedas and their codifications. One part of the Veda codification which contains the teachings of Divinity is the Puranas. This Purana has an important and strategic position in the order of the Vedas and Hindu literature. The purpose of this study was to analyze the divine philosophy teachings in Purana using descriptive qualitative research methods. The conclusions of the research show that the concept of divine philosophy in the Purana shows heterogeneity, almost all the gods are worshiped in the Purana books, as well as popular gods such as Brahma, Vishnu and Shiva which occupy a very high position and give identity to a Purana book. God Almighty takes the form of the holy script Om (Omkara) which is a sound combination of three letters, namely A (Brahma), U (Wisnu), and M (Shiva). the combination (samdhi) of AUM into Om is known as "Pranava" or "Brahman" and all mantras should begin with the letter Om.